Instrumental Behavior in Humans Is Sensitive to the Correlation Between Response Rate and Reward Rate - Perez-Riveros, O (Springer, 2021)
Recent theories of instrumental behavior postulate that the correlation between response and reward rate is a critical factor in instrumental goal-directed performance. However, it is still not clear whether human actions can be sensitive to rate correlation. Using a novel within-subject design, participants were trained under ratio and interval contingencies of reinforcement matching both reward probabilities and reward rates between conditions. The impact of rate correlation on performance was evident in the higher performance observed under ratio contingencies for both types of matching. Moreover, there was no difference in performance between two classes of interval schedules with equivalent correlational properties but different reward probabilities. These results are discussed in terms of a recent dual-system model of instrumental behavior. © 2020, The Psychonomic Society, Inc.